Early ancient sublineages of Mycobacterium tuberculosis Beijing genotype: unexpected clues from phylogenomics of the pathogen and human history. (August 2019) - Mokrousov, I.; Vyazovaya, A.; Pasechnik, O.; Gerasimova, A.; Dymova, M.; Chernyaeva, E.; Tatarintseva, M.; Stasenko, V.
Abstract: Objective: The Mycobacterium tuberculosis Beijing family is an epidemiologically important lineage subdivided into large-scale phylogenetic sublineages: ancient, endemic in East Asia, and global modern. Here, we analysed ancient sublineages of the Beijing genotype in the Omsk region of southwestern Siberia, an intriguing area at the intersection of European Russia, Siberia, and Central Asia. Methods: The study included 423 M. tuberculosis strains isolated in 2013–2017 and subjected to drug susceptibility testing, genotyping, and whole genome sequencing. Results: The Beijing genotype constituted 280 out of 423 strains. Forty Beijing strains belonged to the early ancient sublineage (wild type mutT4 -48). Of these, 11 belonged to the 14717-15 MIRU-VNTR cluster and had intact RD181, 29 belonged to the 1071-32 cluster and had the RD181 deletion. Thirty-nine ancient strains were multidrug-resistant (MDR) and 20 pre-extensively drug resistant (XDR)/XDR. Comparison with global data demonstrated that these clones circulate mainly in Asian Russia with certain phylogenetic affinity to strains from Japan, Korea, and northeastern China. The genome-wide analysis revealed 29–37 single nucleotide polymorphism distances between isolates from different Russian regions within these two clusters. Conclusions: Based on phylogenetic, phylogeographic, genomic, and historical data, we hypothesize that these two clones or their direct ancestors were probably brought to Russia ∼70 years ago after the Second World War with Japanese prisoners of war and, until recently, were mainly circulating in Siberia and the Far East. Their elevated prevalence in Omsk along with the extremely strong association with not only MDR but also pre-XDR/XDR also observed in other locations highlight their epidemic potential and the need for monitoring and attention from health authorities.